Upaya Menurunkan Prokrastinasi Akademik Melalui Bimbingan Klasikal Dengan Teknik Problem Based Learning - Safira Briliana; Isfauzi Hadi Nugroho; Lely Yuanita (Jurnal Pendidikan Sosial Dan Konseling, 2025)
The learning activities carried out by students at school are intended to bring about positive change. However, in practice, these learning activities encounter several obstacles, one of which is the delay in engaging in learning activities. In service delivery activities, it is said to be running well as indicated by the students' active participation in completing assigned tasks. This research was conducted to reduce academic procrastination using the problem-based learning strategy. The research method used is a guidance and counseling action research with an experimental approach. The subjects of the study were 37 students from class X-F. Data collection techniques included observation and questionnaires. The data obtained were analyzed descriptively and comparatively. Based on the analysis results, a decrease in academic procrastination was found, with details showing 67% in the pre-cycle, 63% in cycle I, and 56% in cycle II. It was concluded that the problem-based learning strategy through classical guidance services can reduce academic procrastination